Cut them some slack: Examining the effects of slack resources on the hospital workforce - Frank van de Baan; Niels Hameleers; Rachel Gifford; Bram Fleuren; Dirk Ruwaard; Daan Westra (Health Care Management Review, 2026)
Background: Resource and capacity constraints can hamper the functioning of health care organizations and adversely affect the workforce, particularly during a shock. To mitigate the workforce crisis and enhance the ability to deal with shocks, slack resources (surplus resources accumulated by organizations) may be beneficial. Purpose: This paper seeks to identify how slack may benefit hospital staff in terms of reduced absenteeism and turnover, and how slack may buffer against the negative effects of shocks on staff. Methodology/Approach: Using a nationwide dataset including annual reports of all Dutch hospitals from 2017 to 2021, this paper studies the relationships between three types of slack resources and absenteeism and turnover rates of hospitals. Specifically, linear mixed-effects modeling is used to estimate direct effects of slack resources and to test how COVID-19 (vs. non-COVID-19 years) moderates these resources’ effects based on 342 hospital-year combinations. Results: The analyses reveal a significant curvilinear U-shaped relationship between absorbed slack (i.e., staff levels) and turnover rates. In addition, unabsorbed slack (i.e., financial reserves) and potential slack (i.e., capacity for additional loans) buffered significantly against the increasing effect of COVID-19 on absenteeism rates. Practice Implications: Our study shows that incentivizing health care organizations to acquire slack resources can enable them to reduce turnover rates and, during shocks, mitigate shocks’ adverse impact on absenteeism rates. As such, this studu suggests a need to reconsider the common policies and organizational practices of constraining resources to reduce costs.